2020
DOI: 10.21037/atm-20-405
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative of bleeding, haemolysis and coagulation in mechanical circulatory support patients

Abstract: There are unique complications arising from mechanical support devices but some of the longterm systemic haematological complications are indistinguishable from management problems affecting the care of other patients receiving intermediate to long term care in the cardiac ICU. The field of mechanical cardiac assist device (MCAD) is evolving. Despite major changes in design of these devices the most feared haematological complications have remained unchanged, namely haemolysis, pump thrombosis or thromboemboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Recent areas of interest include: development of new antifibrinolytic agents to reduce bleeding; 31 measurement of platelet function to reduce bleeding and mortality; 32 single or dual agent antiplatelet therapy to maximize bypass graft patency, but increase postoperative bleeding; [33][34][35][36] direct linkage of postoperative cardiac surgical bleeding with increased cost; 4,5 safe and efficacious use of postoperative fibrinogen concentrates; 37,38 role of patient blood management in reducing blood product transfusion and improving cardiac surgical outcomes; 39,40 transfusion reductions associated with the use of prothrombin complex concentrate; 41,42 morbidity associated with reoperation for bleeding following cardiac surgery; 3,43,44 methods of employing thromboelastometry (ROTEM) during cardiac surgery; 45,46 contribution of albumin/gelatin to postoperative bleeding; [47][48][49] advantages of anticoagulation management using thromboelastography (TEG) during cardiopulmonary bypass; [50][51][52] benefit of thrombin inhibitors for pediatric VAD anticoagulation; 53,54 reduction of postoperative blood loss using Unilastin as an antifibrinolytic agent; 55,56 and blood loss leading to multisystem organ failure and hematologic complications following LVAD insertion. 7,57 The CP agent described in this study contains porcine collagen, bovine chondroitin sulfate, and human thrombin. 16 The collagen provides initiation of coagulation and platelet activity, the chondroitin sulfate assists with adherence of the wound to surrounding tissues, and the thrombin adjunctively functions to enhance the conversion of fibrinogen to fibrin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent areas of interest include: development of new antifibrinolytic agents to reduce bleeding; 31 measurement of platelet function to reduce bleeding and mortality; 32 single or dual agent antiplatelet therapy to maximize bypass graft patency, but increase postoperative bleeding; [33][34][35][36] direct linkage of postoperative cardiac surgical bleeding with increased cost; 4,5 safe and efficacious use of postoperative fibrinogen concentrates; 37,38 role of patient blood management in reducing blood product transfusion and improving cardiac surgical outcomes; 39,40 transfusion reductions associated with the use of prothrombin complex concentrate; 41,42 morbidity associated with reoperation for bleeding following cardiac surgery; 3,43,44 methods of employing thromboelastometry (ROTEM) during cardiac surgery; 45,46 contribution of albumin/gelatin to postoperative bleeding; [47][48][49] advantages of anticoagulation management using thromboelastography (TEG) during cardiopulmonary bypass; [50][51][52] benefit of thrombin inhibitors for pediatric VAD anticoagulation; 53,54 reduction of postoperative blood loss using Unilastin as an antifibrinolytic agent; 55,56 and blood loss leading to multisystem organ failure and hematologic complications following LVAD insertion. 7,57 The CP agent described in this study contains porcine collagen, bovine chondroitin sulfate, and human thrombin. 16 The collagen provides initiation of coagulation and platelet activity, the chondroitin sulfate assists with adherence of the wound to surrounding tissues, and the thrombin adjunctively functions to enhance the conversion of fibrinogen to fibrin.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Thus, the risk of bleeding in complex cardiothoracic surgery remains clinically significant and can contribute to: exposure to blood product transfusions; 2 need for re-explorations for bleeding, 3 prolonged lengths of intensive care unit and hospital of stay; 3 increased morbidity and mortality; 3 and larger hospital costs. 4 , 5 Greater patient acuity and procedural complexity as characterized by the emerging use of aggressive antiplatelet therapy 6 and the placement of mechanical assist devices (MCAD) 7 may also contribute to increased risk of postoperative bleeding. In challenging surgical settings, hemostatic agents can be useful adjuncts to the armamentarium available to surgeons for the control of bleeding 8 12 and are known to be useful during cardiothoracic surgical operations.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used TEG to examine the coagulation function in children with KD, and the results showed that the R value and MA were significantly higher in the CAL group than NCAL group, indicating that CAL is closely associated with coagulation dysfunction. The liver is the main organ for the synthesis and metabolism of coagulation factors (12). When the liver was dysfunctional, the synthesis of coagulation factors and heparinase was decreased, the ability to eliminate tissue thrombin and activated fibrinolytic factors was also impaired, and the absorption of vitamin K was also decreased, thus eventually contributed to abnormal clotting (4).…”
Section: Discussionmentioning
confidence: 99%
“…However, adverse events are still common in patients using ECMO. The major presentations are bleeding, thrombosis, and stroke (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%